Palmitoylethanolamide counteracts reactive astrogliosis induced by β-amyloid peptide - Scuderi, Caterina (J Cell Mol Med, 2011)
Emerging evidence indicates that astrogliosis is involved in the pathogenesis of neurodegenerative disorders. Our previous findings suggested cannabinoids and Autacoid Local Injury Antagonism Amides (ALIAmides) attenuate glial response in models of neurodegeneration. The present study was aimed at exploring palmitoylethanolamide (PEA) ability to mitigate β-amyloid (Aβ)-induced astrogliosis. Experiments were carried out to investigate PEA’s (10(−7)M) effects upon the expression and release of pro-inflammatory molecules in rat primary astrocytes activated by soluble Aβ(1–42) (1 μg/ml) as well as to identify mechanisms responsible for such actions. The effects of Aβ and exogenous PEA on the astrocyte levels of the endocannabinoidsand of endogenous ALIAmides were also studied. The peroxisome proliferator-activated receptor (PPAR)-α (MK886, 3 μM) or PPAR-γ (GW9662, 9 nM) antagonists were co-administered with PEA. Aβ elevated endogenous PEA and d5–2-arachidonoylglycerol (2-AG) levels. Exogenous PEA blunted the Aβ-induced expression of pro-inflammatory molecules. This effect was reduced by PPAR-α antagonist. Moreover, this ALIAmide, like Aβ, increased 2-AG levels. These results indicate that PEA exhibits anti-inflammatory properties able to counteract Aβ-induced astrogliosis, and suggest novel treatment for neuroinflammatory/ neurodegenerative processes.